KATA TABU DALAM DIALOG TOKOH PADA FILM BETTER DAYS - Siswantoro, Moh. Yayan; armadani, putri gita (Hasta Wiyata, 2024)
Film is one of the literary works in the form of audio-visual, serving as a medium to convey messages depicted through both sound and images, along with all its supporting elements. The term 'taboo' is one of the sociolinguistic studies that we often hear; generally, taboo words go against the prevailing norms and moral values. In this research, the author aims to explore what kind of taboo words are present in the film 'Better Days' and classify them according to their types. The goal is to identify the types of taboo words used in the dialogue between characters, using the taboo word classification according to The Jay.